Differences in Children’s Nutritional Knowledge Level and Parent’s Characteristics in Obese and Non-Obese Adolescents of Permai Pluit Junior High School - Tena Djuartina; Sylvia Wijaya; Andreas Steven; Syarief Darmawan (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
Obesity is a major health problem among children. The etiology of childhood obesity is multifactorial and it leads to many complications in adulthood.This study aimed to assess the differences in nutritional knowledge and characteristics of parents in obese and non-obese adolescents. This case control descriptive research was conducted on all students of Permai Pluit Junior High School and their parents. Nutritional knowledge and characteristics of parents were obtained by self-report using a questionnaire. The weight and height of the subjects were measured according to standard methods and body mass index was calculated, then assessed with CDC growth charts. Data were analyzed using chi square, Kolmogorov Smirnov, and Fisher Exact test; significance level was set at 0.05. The prevalence of obesity was 18.21%. There was no significant relationship between nutritional knowledge of parents and nutritional status of adolescent (p = 0.750). There was also no significant relationships between characteristics of parents and nutritional status of adolescents (mothers’ education, p = 0.907; fathers’ education, p = 0.203, mothers’ occupation, p = 0,627, fathers’ occupation, p = 0.151). In conclusion, there is no relationship between neither nutritional knowledge nor characteristics of parents and nutritional status of adolescents.